2021
DOI: 10.3390/pharmaceutics13101584
|View full text |Cite
|
Sign up to set email alerts
|

Egr1 Gene Expression as a Potential Biomarker for In Vitro Prediction of Ocular Toxicity

Abstract: Animal models are used for preclinical toxicity studies, and the need for in vitro alternative methods has been strongly raised. Our study aims to elucidate the potential mechanism of change in EGR1 expression under situations of toxic injury and to develop an Egr1 promoter–luciferase gene reporter assay for an in vitro alternative method for toxicity prediction in drug discovery. We first found an increase in early growth response-1 (EGR1) mRNA/protein expressions in the liver and kidney of cisplatin-treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Previous studies reported that EGR1 is the downstream target of LIF-STAT3 signaling and ERK signaling. 52 , 53 , 54 , 55 , 56 , 57 Accordingly, depletion of LIFR or EGR1 by siRNA diminished LIF-augmented SHH expression, indicating that SHH is a downstream target of LIF-LIFR-EGR1 axis in renal tubular cells ( Fig. 5 d–g).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Previous studies reported that EGR1 is the downstream target of LIF-STAT3 signaling and ERK signaling. 52 , 53 , 54 , 55 , 56 , 57 Accordingly, depletion of LIFR or EGR1 by siRNA diminished LIF-augmented SHH expression, indicating that SHH is a downstream target of LIF-LIFR-EGR1 axis in renal tubular cells ( Fig. 5 d–g).…”
Section: Resultsmentioning
confidence: 82%
“…Since EGR1 is the downstream target of ERK signaling and STAT3 signaling, 52 , 53 , 54 , 55 , 56 , 57 we sought LIF expression might be up-regulated by an autocrine pathway in fibroblasts. As expected, when NRK49F cells were incubated with indicated concentration of LIF for 24 h, both mRNA and protein level of LIF was increased in a dose-dependent manner ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since activation of the MAPK/c-Jun pathway can promote the expression of EGR1 [ 21 , 22 ], we examined EGR1 expression and photoreceptor death after administration of the JNK inhibitor tanzisertib and ERK inhibitor PD98059. Western blotting and the TUNEL assay were used as readouts.…”
Section: Resultsmentioning
confidence: 99%